2013
DOI: 10.1161/circresaha.111.247940
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Ion Channels by Pyridine Nucleotides

Abstract: Recent research suggests that in addition to their role as soluble electron carriers, pyridine nucleotides [NAD(P)(H)] also regulate ion transport mechanisms. This mode of regulation seems to have been conserved through evolution. Several bacterial ion–transporting proteins or their auxiliary subunits possess nucleotide-binding domains. In eukaryotes, the Kv1 and Kv4 channels interact with pyridine nucleotide–binding β-subunits that belong to the aldo-keto reductase superfamily. Binding of NADP+ to Kvβ removes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
60
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(62 citation statements)
references
References 134 publications
(195 reference statements)
0
60
0
2
Order By: Relevance
“…We also observed a significant increase in basal levels of NAD(P)H autofluorescence in Ndufs2-null glomus cells with respect to controls ( Figure 7I). Numerous reports have indicated that pyridine nucleotides can bind to voltage-gated K + channel subunits and modulate their function (Tipparaju et al, 2005;Tamsett et al, 2009;Kilfoil et al, 2013). Loading glomus cells with NADH (150 mM in the whole-cell recording pipette), thereby mimicking the conditions that may exist in Ndufs2-deficient mice, markedly blunted the hypoxic modulation of the currents (Figures S7I and S7J).…”
Section: Mitochondrial Complex I Signaling To Membrane K + Channels Imentioning
confidence: 94%
“…We also observed a significant increase in basal levels of NAD(P)H autofluorescence in Ndufs2-null glomus cells with respect to controls ( Figure 7I). Numerous reports have indicated that pyridine nucleotides can bind to voltage-gated K + channel subunits and modulate their function (Tipparaju et al, 2005;Tamsett et al, 2009;Kilfoil et al, 2013). Loading glomus cells with NADH (150 mM in the whole-cell recording pipette), thereby mimicking the conditions that may exist in Ndufs2-deficient mice, markedly blunted the hypoxic modulation of the currents (Figures S7I and S7J).…”
Section: Mitochondrial Complex I Signaling To Membrane K + Channels Imentioning
confidence: 94%
“…Cellular redox status is an important determinant of cardiac function. Pyridine nucleotides that are major intracellular redox modulators regulate the Kv channel activity (3, 22, 24). Given the significant structural and ion channel disturbances reported in hyperoxia treated mouse hearts, we hypothesize that hyperoxia exposure leads to cardiac ion channel disturbances and redox changes resulting in arrhythmias.…”
Section: Introductionmentioning
confidence: 99%
“…Pyridine nucleotides have recently been hypothesized to be essential for sensing oxygen levels and metabolite availability (20). One of these, nicotinic acid adenine dinucleotide phosphate is the most potent intracellular Ca 2ϩ mobilizer identified to date (21)(22)(23).…”
mentioning
confidence: 99%